Application of a narrow distribution double nano composite detergent in improving crankcase sludge deposition of lubricating oil

CN122979020APending Publication Date: 2026-10-27JIANGSU AORUN ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611081210.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明针对现有磷酸钙/水杨酸钙复配清净剂体系存在的胶束粒径分布宽、高温易絮凝、油泥易沉积、曲轴箱模拟成焦量大及漆膜评级差等技术缺陷,提供一种窄分布双纳米复合清净剂在润滑油改善曲轴箱油泥沉积的应用

Benefits of technology

第一、胶束粒径窄分布:本发明的复合清净剂通过采用双纳米颗粒(亲油改性纳米氮化硼与窄分布纳米碳酸钙)协同改性复合清净体系,亲油改性纳米氮化硼(片状结构)与窄分布纳米碳酸钙(粒状结构)在复合胶束体系中扮演“纳米骨架”角色。两种不同形貌的纳米颗粒穿插于磷酸钙/水杨酸钙胶束之间,通过空间位阻效应限制胶束的过度生长与团聚,使胶束粒径趋于均匀——即实现“窄分布”,从而大幅提升高温胶束结构稳定性,避免高温絮凝分层。亲油改性纳米氮化硼表面的亲油聚合物刷在油相中充分伸展,形成空间位阻层,有效阻止油泥微粒在胶束表面的吸附与团聚。纳米碳酸钙则通过其表面碱性位点中和酸性油泥前驱物,从源头减少油泥生成。两者协同作用,阻断油泥微粒的团聚粘附。纳米氮化硼具有优异的高温稳定性和固体润滑性能,在高温工况下保持结构稳定;纳米碳酸钙则在低温条件下具有良好的分散活性。两者协同,兼顾了油品在高低温条件下的清净分散需求。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of lubricating oil additives, and particularly relates to application of a narrow-distribution double-nano composite detergent in improving crankcase sludge deposition of lubricating oil. The composite detergent comprises the following raw material components: high-alkaline calcium alkyl sulfonate, medium-alkaline alkyl salicylate, oil-wetting modified nano boron nitride, narrow-distribution nano calcium carbonate and alkyl aromatic hydrocarbon auxiliary dispersant regulator. The composite detergent has strong formula compatibility, simple preparation process and low mass production cost, can be directly adapted to the existing lubricating oil production system, and does not need large-scale modification of the production line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lubricating oil additive technology, specifically, it relates to the application of a narrow-distribution dual-nano composite detergent in improving crankcase sludge deposition in lubricating oil. Background Technology

[0002] Under the high-temperature, aerobic conditions of the crankcase, internal combustion engine oils, including base oils and additives, are prone to oxidation and condensation reactions, generating sludge precursors such as gum and carbon particles. This leads to piston varnish and carbon deposits, severely affecting engine cleanliness and oil lifespan. Detergents, as the most widely used additive in internal combustion engine oils, play a crucial role in neutralizing acidic substances produced by lubricant oxidation and fuel combustion, removing particulate contaminants from inside the engine, and inhibiting deposit formation. Currently, widely used detergents in the industry mainly include sulfonates, sulfurized alkylphenol salts, and alkyl salicylates, among which the compound system of high-base calcium sulfonate and salicylates is one of the mainstream technical routes.

[0003] However, existing calcium phosphate / calcium salicylate compound systems suffer from several insurmountable technical drawbacks. First, the micelle size distribution of this system is relatively wide, making them prone to flocculation and aggregation under high-temperature conditions, leading to sludge deposition. Second, although some studies have attempted to improve detergency by incorporating nanomaterials, simple incorporation of nanomaterials has poor compatibility with the micelle system, easily disrupting the original stable micelle structure and causing storage stratification. Furthermore, under the SH / T 0300 crankcase simulation test conditions, existing systems exhibit high aluminum plate coking and low varnish ratings, failing to meet increasingly stringent engine cleanliness requirements. Finally, while improving detergency, most existing technical solutions inevitably increase oil ash content or exacerbate metal corrosion, making them unsuitable for current low-ash environmentally friendly oil standards.

[0004] To address the issues of precipitation and poor dispersibility when salicylates and sulfonates are combined, previous studies have proposed a one-step synthesis method to fuse them into a mixed matrix detergent. Patent literature also discloses a method for preparing ultra-high alkalinity composite calcium salt detergents, which improves the precipitation problem when calcium sulfonate and calcium salicylate are combined by mixing sulfonic acid, salicylic acid, and inorganic calcium followed by neutralization and carbonation reactions. Furthermore, the application of nano-calcium carbonate in the lubrication field has been reported, and research on nano-boron nitride as a lubricating oil additive has also made some progress. However, none of the above technologies have solved the core problems of wide micelle size distribution, poor high-temperature stability, and easy agglomeration and deposition of sludge, nor have they achieved the technical effect of narrow distribution through synergistic regulation of the micelle microstructure by nanoparticles.

[0005] Therefore, developing a novel detergent system that can significantly improve crankcase sludge deposition performance without increasing ash content and corrosivity has significant industrial application value. Summary of the Invention

[0006] This invention addresses the technical shortcomings of existing calcium phosphate / calcium salicylate compound detergent systems, such as wide micelle size distribution, easy flocculation at high temperatures, easy sludge deposition, high simulated coking volume in crankcases, and poor varnish rating. It provides a narrow-distribution dual-nano composite detergent for improving crankcase sludge deposition in lubricating oils. This invention utilizes lipophilic modified dual nanoparticles (nano boron nitride and nano calcium carbonate) to synergistically regulate the microstructure of the calcium phosphate / salicylate composite micelles, significantly improving the high and low temperature sludge dispersion performance, high-temperature anti-deposition ability, and long-term storage stability of oils while ensuring low ash content and low metal corrosion.

[0007] Therefore, the present invention provides the following technical solution.

[0008] The first aspect of the present invention provides a narrow-distribution dual-nano composite detergent comprising the following raw material components: high-alkali alkyl sulfonate calcium, medium-alkali alkyl salicylate, lipophilic modified nano boron nitride, narrow-distribution nano calcium carbonate, and alkyl aromatic hydrocarbon dispersant regulator; The total alkalinity of the high-alkalinity alkyl sulfonate calcium is 280~410 mgKOH / g; The total alkalinity of the medium-alkalinity alkyl salicylate calcium is 150~250 mgKOH / g; The average particle size of the lipophilic modified boron nitride nanoparticles is 20~100 nm; the surface of the lipophilic modified boron nitride nanoparticles has a chemically anchored inner shell layer and a lipophilic polymer brush outer shell layer arranged sequentially from the inside to the outside. The narrow-distribution nano-calcium carbonate has an average particle size of 10~50 nm and a particle size polydispersity index (PDI) ≤0.3.

[0009] In a preferred embodiment of the present invention, the proportions of each component by weight are as follows: 30-60 parts of high-alkalinity alkyl sulfonate calcium, 20-50 parts of medium-alkalinity alkyl salicylate calcium, 1-10 parts of lipophilic modified nano boron nitride, 1-10 parts of narrow-distribution nano calcium carbonate, and 5-10 parts of alkyl aromatic hydrocarbon dispersant.

[0010] In a preferred embodiment of the present invention, the alkyl aromatic dispersant is selected from one or more of C10-C20 alkylbenzenes and light mineral oils.

[0011] In a preferred embodiment of the present invention, the lipophilic modified boron nitride nanoparticles are prepared according to the following steps: S1: Disperse hexagonal boron nitride powder in a strong alkaline solution at a mass-volume ratio of 1g:10~30mL, and carry out a hydrothermal reaction at 80~120℃ for 6~24 h to hydrolyze some of the BN bonds on its surface to form boron hydroxyl active sites, thereby obtaining hydroxylated boron nitride nanosheets. S2: The obtained hydroxylated boron nitride nanosheets were dispersed in an organic solvent at a mass-volume ratio of 1g:10~50mL to obtain a boron nitride suspension; a tetracarboxylic acid ligand and a silane coupling agent were added to the obtained boron nitride suspension and stirred to react. After the reaction was completed, the mixture was cooled to room temperature and filtered. Water was added to the obtained precipitate and the mixture was sonicated at 600~800W for 10~30min. Finally, the mixture was filtered and dried to obtain modified boron nitride nanosheets. S3: The obtained modified boron nitride nanosheets were dispersed in an organic solvent at a mass-volume ratio of 1g:20~60mL. Polyisobutylene succinimide was added and stirred evenly at 60~65℃. Then, lipophilic monomers and initiators were added and stirred for reaction. After the reaction was completed, crosslinking agent was added and stirring was continued for 1~3h. Finally, the obtained product was centrifuged, washed with solvent and vacuum dried to obtain lipophilic modified boron nitride nanosheets.

[0012] In the preparation process of the above-mentioned lipophilic modified boron nitride nanosheets, in step S1, hexagonal boron nitride (h-BN) has a graphite-like layered structure, consisting of a six-membered ring planar network formed by BN covalent bonds, with the layers bonded by van der Waals forces. Under strongly alkaline hydrothermal conditions, the BN bonds on the surface and edges of the boron nitride nanosheets undergo hydrolysis, and the B atoms react with OH groups. - The nitrogen atom is released as NH3, forming boron hydroxyl groups (B-OH). Studies have shown that the -OH groups preferentially bind to the B sites on the surface of h-BN. After hydrothermal hydroxylation treatment, a large number of B-OH active sites are formed on the surface of boron nitride nanosheets, providing a reaction basis for subsequent chemical anchoring.

[0013] In step S2, the silane coupling agent (taking methyltrimethoxysilane as an example) first undergoes a hydrolysis reaction in the reaction system. The methoxy group (-OCH3) hydrolyzes to generate silanol groups (Si-OH). The generated silanol groups undergo dehydration condensation to form oligomers containing Si-OH active groups. The Si-OH groups in the silane coupling agent oligomer undergo a dehydration condensation reaction with the B-OH on the surface of the boron nitride nanosheets to form stable Si-OB covalent bonds, covalently anchoring the silane coupling agent to the boron nitride surface. This covalent bonding method differs from ordinary physical adsorption, exhibiting strong and irreversible characteristics, providing a stable chemical linking layer for subsequent functionalization. The tetracarboxylic acid ligand molecule contains four carboxyl (-COOH) functional groups. On one hand, the carboxyl groups can form hydrogen bonds or coordination interactions with the B-OH on the boron nitride surface; on the other hand, the carboxyl groups can also undergo esterification or hydrogen bond interactions with active groups (such as residual hydroxyl groups) in the silane coupling agent molecule. The tetracarboxylic ligand and the silane coupling agent together form a dual-ligand synergistic anchoring layer on the boron nitride surface. The silane coupling agent provides covalent anchoring, while the tetracarboxylic ligand increases the density of surface active sites and regulates the interfacial chemical environment through polydentate coordination, creating favorable conditions for the graft polymerization of lipophilic monomers in step S3.

[0014] In step S3, a lipophilic polymer brush shell layer is grafted onto the surface of boron nitride nanosheets through free radical polymerization. The reaction mechanism is as follows: (1) Anchoring of polyisobutylene succinimide: The polyisobutylene succinimide (PIBS) molecule contains a succinimide polar head and a long-chain polyisobutylene lipophilic tail. Its polar head is bonded to the double ligand anchoring layer (tetracarboxylic ligand / silane coupling agent layer) formed in step S2 through hydrogen bonds or chemical bonds, anchoring PIBS to the surface of boron nitride. The anchoring of PIBS not only increases the surface lipophilicity, but the double bonds or active hydrogen in its molecule can also participate in the subsequent graft polymerization reaction. (2) Free radical graft polymerization of lipophilic monomers: Under the action of an initiator, lipophilic monomers (such as butyl acrylate, isooctyl acrylate, lauryl acrylate, octadecyl acrylate, etc.) undergo free radical polymerization. The polymerization reaction takes place in situ on the surface of boron nitride. The active sites in the anchored PIBS molecules can serve as "anchor points" for polymerization, allowing polymer chains to grow outward from the surface and form an oleophilic polymer brush. (3) Crosslinking and curing of crosslinking agents: The added crosslinking agents (such as toluene diisocyanate) play a crosslinking and curing role in the polymer brush layer. Isocyanate groups (-NCO) can react with active hydrogen (such as hydroxyl and amino groups) in the polymer chain to form a crosslinked network structure, which enhances the structural stability and density of the polymer brush layer.

[0015] In a preferred embodiment of the present invention, in step S1, the strong alkaline solution is selected from sodium hydroxide solution or potassium hydroxide solution, and the concentration is 2~10 mol / L.

[0016] In a preferred embodiment of the present invention, in step S2, the organic solvent is selected from toluene, ethanol, and tetrahydrofuran.

[0017] In a preferred embodiment of the present invention, in step S2, the tetracarboxylic ligand is selected from any one of 3,3',5,5'-sulfinyl diisophthalic acid, 3,3',5,5'-sulfonyl diisophthalic acid, 3,3',5,5'-azadiisophthalic acid, 3,3',5,5'-oxodiisophthalic acid, 3,3',5,5'-carbonyl diisophthalic acid, and 3,3',5,5'-methylene diisophthalic acid.

[0018] In a preferred embodiment of the present invention, in step S2, the amount of the tetracarboxylic ligand added is 0.3 to 0.5 times the mass of the hydroxylated boron nitride nanosheets.

[0019] In a preferred embodiment of the present invention, in step S2, the silane coupling agent is selected from one or more of methyltrimethoxysilane, tetramethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltriethoxysilane, and tetrapropoxysilane.

[0020] In a preferred embodiment of the present invention, in step S2, the amount of silane coupling agent added is 0.1 to 0.5% of the mass of the hydroxylated boron nitride nanosheets.

[0021] In a preferred embodiment of the present invention, in step S3, the organic solvent is selected from toluene, ethanol, and tetrahydrofuran.

[0022] In a preferred embodiment of the present invention, in step S3, the amount of polyisobutylene succinimide added is 5 to 30% of the mass of the modified boron nitride nanosheets.

[0023] In a preferred embodiment of the present invention, in step S3, the lipophilic monomer is selected from one or more of butyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate.

[0024] In a preferred embodiment of the present invention, in step S3, the amount of the lipophilic monomer added is 1 to 3 times the mass of the modified boron nitride nanosheets.

[0025] In a preferred embodiment of the present invention, in step S3, the initiator is selected from one or more of ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, and azobisisobutyronitrile.

[0026] In a preferred embodiment of the present invention, in step S3, the amount of initiator added is 0.2 to 0.7% of the mass of the lipophilic monomer.

[0027] In a preferred embodiment of the present invention, in step S3, the crosslinking agent is selected from one or more of toluene diisocyanate, chlorophenyl diisocyanate, tetramethylene diisocyanate, phenyl dimethylene diisocyanate, and diphenylmethane diisocyanate.

[0028] In a preferred embodiment of the present invention, in step S3, the amount of crosslinking agent added is 0.1 to 0.3% of the mass of polyisobutylene succinimide.

[0029] A second aspect of the present invention provides a method for preparing a narrow-distribution dual-nano composite detergent as described above, comprising the following steps: (1) Under nitrogen protection, high-base-value alkyl sulfonate calcium and medium-base-value alkyl salicylate calcium are added to the reaction vessel in proportion and dehydrated at low temperature at 60~100℃ to obtain the base compound system; (2) The lipophilic modified boron nitride nanoparticles and narrowly distributed calcium carbonate nanoparticles are pre-dispersed ultrasonically in a portion of alkyl aromatic hydrocarbon dispersant to form two pre-dispersed suspensions, namely lipophilic modified boron nitride nanoparticles and narrowly distributed calcium carbonate nanoparticles suspensions. (3) Under stirring conditions, the two pre-dispersed nano suspensions were added to the substrate compound system in steps, and then the high-speed homogeneous stirring dispersion process was used to treat the mixture at a speed of 3000~10000 rpm for 30~120 min to obtain a narrow distribution dual nano composite detergent.

[0030] A third aspect of the present invention provides the application of the narrow-distribution dual-nano composite detergent as described above in lubricating oil, wherein the detergent is added to the base oil at a mass ratio of 3.0% to 6.0% and used in conjunction with conventional lubricating oil additives.

[0031] In a preferred embodiment of the present invention, the lubricating oil is an internal combustion engine oil, the detergent is used to improve the sludge deposition performance of the crankcase, and the lubricating oil with the detergent added has a coking amount of ≤10 mg on aluminum plate and a varnish rating of ≤2 in the SH / T 0300 crankcase simulation test.

[0032] By employing the above technical solution, the present invention has at least the following advantages: First, the micelles exhibit a narrow particle size distribution: The composite detergent of this invention employs dual nanoparticles (lipophilic modified boron nitride nanoparticles and narrowly distributed calcium carbonate nanoparticles) to synergistically modify the composite detergent system. The lipophilic modified boron nitride nanoparticles (plate-like structure) and the narrowly distributed calcium carbonate nanoparticles (granular structure) act as a "nanoskeleton" in the composite micelle system. These two different morphologies of nanoparticles interspersed between calcium phosphate / calcium salicylate micelles, limiting excessive growth and aggregation of micelles through steric hindrance, resulting in a more uniform micelle size—that is, achieving a "narrow distribution." This significantly improves the structural stability of the high-temperature micelles and prevents high-temperature flocculation and stratification. The lipophilic polymer brushes on the surface of the lipophilic modified boron nitride nanoparticles fully extend in the oil phase, forming a steric hindrance layer that effectively prevents the adsorption and aggregation of sludge particles on the micelle surface. The nano-calcium carbonate, through its surface alkaline sites, neutralizes acidic sludge precursors, reducing sludge formation at the source. The synergistic effect of both prevents the aggregation and adhesion of sludge particles. Nano-boron nitride exhibits excellent high-temperature stability and solid lubrication properties, maintaining structural stability under high-temperature conditions; while nano-calcium carbonate demonstrates good dispersing activity at low temperatures. The synergy of these two materials addresses the detergency and dispersion requirements of oils under both high and low temperature conditions.

[0033] Second, excellent anti-sludge deposition performance: The composite detergent of this invention relies on the adsorption and isolation effect of the nano-interface to block the agglomeration and adhesion of sludge particles, significantly reduce the amount of coking in the crankcase simulation test and improve the smoothness of the paint film. It shows excellent anti-deposition performance in the SH / T 0300 crankcase simulation test.

[0034] Third, low ash content and low corrosion: The composite detergent of this invention combines the high and low temperature performance advantages of calcium phosphate and salicylate, while taking into account the characteristics of low ash content and low corrosion, meeting the requirements of the current low-ash environmentally friendly oil standards.

[0035] Fourth, good formula compatibility and process adaptability: The composite detergent of the present invention has strong formula compatibility, simple preparation process, and low mass production cost. It can be directly adapted to the existing lubricating oil production system without the need for large-scale modification of the production line.

[0036] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Detailed Implementation

[0037] To make the technical means, creative features, achieved objectives, and effects of this invention readily understandable, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0038] The detection methods involved in the following embodiments include: Test Method Description (1) Micellar particle size distribution (PDI): The polydispersity index of the micelles of detergent in base oil was determined by dynamic light scattering particle size analyzer. The smaller the PDI value, the narrower and more uniform the particle size distribution.

[0039] (2) Coking amount of aluminum plate: The coking amount of aluminum plate is determined according to SH / T 0300 "Crankcase Simulation Test Method (QZX Method)". The test aluminum plate is placed in the crankcase simulation test machine and run under the specified temperature and time conditions. The coking mass of aluminum plate is then weighed.

[0040] (3) Coating film rating: The coating film condition of the aluminum plate surface after the test is rated according to the SH / T 0300 method. Grade 1 is the best (slight coating) and Grade 4 is the worst (severe coating).

[0041] (4) High temperature storage stability: After adding the detergent to the base oil, place it in a constant temperature oven at 100℃ for 72 hours and observe whether there is stratification, sedimentation or flocculation.

[0042] (5) Ash content: The determination was carried out in accordance with GB / T 2433-2001 "Determination of sulfate ash content in lubricating oil".

[0043] Example 1: Narrowly Distributed Dual-Nano Composite Detergent I and its Preparation Preparation of lipophilic modified boron nitride nanosheets: Hexagonal boron nitride powder (200 nm in diameter) was dispersed in a 6 mol / L sodium hydroxide solution at a mass-volume ratio of 1 g: 20 mL. The mixture was subjected to a hydrothermal reaction at 100 °C for 15 h in a hydrothermal reactor to hydrolyze some of the BN bonds on the surface to form boron hydroxyl active sites. After the reaction was completed, the product was washed with deionized water until neutral and then vacuum dried at 60 °C to obtain hydroxylated boron nitride nanosheets. The obtained hydroxylated boron nitride nanosheets were dispersed in toluene at a mass-to-volume ratio of 1 g: 30 mL to obtain a boron nitride suspension. 3,3',5,5'-sulfinyl diisophthalic acid (0.4 times the mass of the hydroxylated boron nitride nanosheets) and dimethyldiethoxysilane (0.3% of the mass of the hydroxylated boron nitride nanosheets) were added to the obtained boron nitride suspension and stirred at 70 °C under a nitrogen atmosphere for 8 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. Deionized water was added to the obtained precipitate and the mixture was sonicated at 700 W for 20 min. Finally, the mixture was filtered and dried to obtain modified boron nitride nanosheets. The modified boron nitride nanosheets were dispersed in toluene at a mass-to-volume ratio of 1 g: 40 mL. Polyisobutylene succinimide (18% of the mass of the modified boron nitride nanosheets) was added and stirred at 65 °C until homogeneous. Then, butyl acrylate (twice the mass of the modified boron nitride nanosheets) and benzoyl peroxide (0.5% of the mass of butyl acrylate) were added and stirred at 70 °C for 4 h. After the reaction was completed, phthalimide diisocyanate (0.2% of the mass of polyisobutylene succinimide) was added and stirring was continued for 2 h. Finally, the obtained product was centrifuged, washed with toluene solvent, and vacuum dried at 60 °C to obtain oleophilic modified boron nitride nanosheets.

[0044] Preparation of a narrow-distribution dual-nano composite detergent: The following components were weighed by weight: 45 parts of high-alkalinity alkyl sulfonate calcium (total alkalinity 340 mgKOH / g), 35 parts of medium-alkalinity alkyl salicylate calcium (total alkalinity 200 mgKOH / g), 5 parts of lipophilic modified nano-boron nitride (average particle size 50 nm), 5 parts of narrow-distribution nano-calcium carbonate (average particle size 30 nm, polydispersity index PDI ≤ 0.3), and 10 parts of alkyl aromatic hydrocarbon co-dispersant (C12 alkylbenzene). Under nitrogen protection, the high-alkalinity alkyl sulfonate calcium and medium-alkalinity alkyl salicylate calcium were added to a reaction vessel according to the specified ratio, and low-temperature dehydration was carried out at 80℃ to obtain the base composite system. The lipophilic modified nano-boron nitride and narrow-distribution nano-calcium carbonate were pre-dispersed ultrasonically in 5 parts of the alkyl aromatic hydrocarbon co-dispersant to form two pre-dispersed suspensions: a lipophilic modified nano-boron nitride suspension and a narrow-distribution nano-calcium carbonate suspension. Under stirring conditions, the two pre-dispersed nano suspensions were added to the substrate composite system in steps, and then treated with a high-speed homogenization stirring dispersion process at 6000 rpm for 70 min to obtain narrow-distribution dual nanocomposite detergent I.

[0045] Example 2: Narrowly Distributed Dual-Nano Composite Detergent II and Its Preparation Preparation of lipophilic modified boron nitride nanosheets: Hexagonal boron nitride powder (200 nm in diameter) was dispersed in a 2 mol / L sodium hydroxide solution at a mass-volume ratio of 1 g: 30 mL. The mixture was subjected to a hydrothermal reaction at 120 °C for 6 h in a hydrothermal reactor to hydrolyze some of the BN bonds on the surface to form boron hydroxyl active sites. After the reaction was completed, the product was washed with deionized water until neutral and then vacuum dried at 60 °C to obtain hydroxylated boron nitride nanosheets. The obtained hydroxylated boron nitride nanosheets were dispersed in tetrahydrofuran at a mass-to-volume ratio of 1 g: 10 mL to obtain a boron nitride suspension. 3,3',5,5'-sulfonyl diisophthalic acid (0.3 times the mass of the hydroxylated boron nitride nanosheets) and methyltriethoxysilane (0.1% of the mass of the hydroxylated boron nitride nanosheets) were added to the obtained boron nitride suspension and stirred at 80 °C under a nitrogen atmosphere for 6 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. Deionized water was added to the obtained precipitate and the mixture was sonicated at 600 W for 30 min. Finally, the mixture was filtered and dried to obtain modified boron nitride nanosheets. The modified boron nitride nanosheets were dispersed in tetrahydrofuran at a mass-to-volume ratio of 1 g: 60 mL. Polyisobutylene succinimide (30% of the mass of the modified boron nitride nanosheets) was added and stirred at 60 °C until homogeneous. Then, isooctyl acrylate (3 times the mass of the modified boron nitride nanosheets) and benzoyl peroxide (0.7% of the mass of isooctyl acrylate) were added and stirred at 70 °C for 6 h. After the reaction was completed, tetramethylene diisocyanate (0.3% of the mass of polyisobutylene succinimide) was added and stirring was continued for 3 h. Finally, the obtained product was centrifuged, washed with toluene solvent, and vacuum dried at 60 °C to obtain lipophilic modified boron nitride nanosheets.

[0046] Preparation of a narrow-distribution dual-nano composite detergent: The following components were weighed by weight: 30 parts of high-alkalinity alkyl sulfonate calcium (total alkalinity 410 mg KOH / g), 50 parts of medium-alkalinity alkyl salicylate calcium (total alkalinity 150 mg KOH / g), 1 part of lipophilic modified nano-boron nitride (average particle size 100 nm), 10 parts of narrow-distribution nano-calcium carbonate (average particle size 10 nm, polydispersity index PDI ≤ 0.3), and 9 parts of alkyl aromatic hydrocarbon co-dispersant (C20 alkylbenzene). Under nitrogen protection, the high-alkalinity alkyl sulfonate calcium and medium-alkalinity alkyl salicylate calcium were added to a reaction vessel according to the specified ratio and subjected to low-temperature dehydration at 60℃ to obtain the base composite system. The lipophilic modified nano-boron nitride and narrow-distribution nano-calcium carbonate were pre-dispersed ultrasonically in a portion of the alkyl aromatic hydrocarbon co-dispersant to form two pre-dispersed suspensions: a lipophilic modified nano-boron nitride suspension and a narrow-distribution nano-calcium carbonate suspension. Under stirring conditions, the two pre-dispersed nano suspensions were added to the substrate composite system in steps, and then treated with a high-speed homogenization stirring dispersion process at 10,000 rpm for 30 min to obtain narrow-distribution dual nanocomposite detergent II.

[0047] Example 3: Narrowly Distributed Dual-Nano Composite Detergent III and Its Preparation Preparation of lipophilic modified boron nitride nanosheets: Hexagonal boron nitride powder (200 nm in diameter) was dispersed in a 10 mol / L sodium hydroxide solution at a mass-volume ratio of 1 g: 10 mL. The mixture was subjected to a hydrothermal reaction at 80 °C for 24 h in a hydrothermal reactor to hydrolyze some of the BN bonds on the surface to form boron hydroxyl active sites. After the reaction was completed, the product was washed with deionized water until neutral and then vacuum dried at 60 °C to obtain hydroxylated boron nitride nanosheets. The obtained hydroxylated boron nitride nanosheets were dispersed in ethanol at a mass-to-volume ratio of 1 g: 50 mL to obtain a boron nitride suspension. 3,3',5,5'-methylene isophthalic acid (0.5 times the mass of the hydroxylated boron nitride nanosheets) and methyltrimethoxysilane (0.5% of the mass of the hydroxylated boron nitride nanosheets) were added to the obtained boron nitride suspension and stirred at 60 °C under a nitrogen atmosphere for 10 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. Deionized water was added to the obtained precipitate and the mixture was sonicated at 800 W for 10 min. Finally, the mixture was filtered and dried to obtain modified boron nitride nanosheets. The modified boron nitride nanosheets were dispersed in ethanol at a mass-to-volume ratio of 1 g: 20 mL. Polyisobutylene succinimide (5% of the mass of the modified boron nitride nanosheets) was added and stirred at 60 °C until homogeneous. Then, lauryl acrylate (1 times the mass of the modified boron nitride nanosheets) and azobisisobutyronitrile (0.2% of the mass of lauryl acrylate) were added and stirred at 60 °C for 5 h. After the reaction was completed, toluene diisocyanate (0.1% of the mass of polyisobutylene succinimide) was added and stirring was continued for 1 h. Finally, the obtained product was centrifuged, washed with toluene solvent, and vacuum dried at 60 °C to obtain lipophilic modified boron nitride nanosheets.

[0048] Preparation of a narrow-distribution dual-nano composite detergent: The following components were weighed by weight: 60 parts of high-alkalinity alkyl sulfonate calcium (total alkalinity 280 mg KOH / g), 20 parts of medium-alkalinity alkyl salicylate calcium (total alkalinity 250 mg KOH / g), 10 parts of lipophilic modified nano-boron nitride (average particle size 20 nm), 1 part of narrow-distribution nano-calcium carbonate (average particle size 50 nm, polydispersity index PDI ≤ 0.3), and 9 parts of alkyl aromatic hydrocarbon co-dispersant (C10 alkylbenzene). Under nitrogen protection, the high-alkalinity alkyl sulfonate calcium and medium-alkalinity alkyl salicylate calcium were added to a reaction vessel according to the specified ratio and subjected to low-temperature dehydration at 100℃ to obtain the base composite system. The lipophilic modified nano-boron nitride and narrow-distribution nano-calcium carbonate were pre-dispersed ultrasonically in a portion of the alkyl aromatic hydrocarbon co-dispersant to form two pre-dispersed suspensions: a lipophilic modified nano-boron nitride suspension and a narrow-distribution nano-calcium carbonate suspension. Under stirring conditions, the two pre-dispersed nano suspensions were added to the substrate composite system in steps, and then treated with a high-speed homogenization stirring dispersion process at 3000 rpm for 120 min to obtain narrow-distribution dual nanocomposite detergent III.

[0049] Comparative Example 1: Composite Detergent I and its Preparation Preparation of lipophilic modified boron nitride nanosheets: Hexagonal boron nitride powder (200 nm in diameter) was dispersed in toluene at a mass-to-volume ratio of 1 g: 30 mL to obtain a boron nitride suspension. 3,3',5,5'-sulfinyl diisophthalic acid (0.4 times the mass of the hydroxylated boron nitride nanosheets) and dimethyldiethoxysilane (0.3% of the mass of the hydroxylated boron nitride nanosheets) were added to the obtained boron nitride suspension and stirred at 70 °C under a nitrogen atmosphere for 8 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. Deionized water was added to the obtained precipitate and the mixture was sonicated at 700 W for 20 min. Finally, the mixture was filtered and dried to obtain modified boron nitride nanosheets. The modified boron nitride nanosheets were dispersed in toluene at a mass-to-volume ratio of 1 g: 40 mL. Polyisobutylene succinimide (18% of the mass of the modified boron nitride nanosheets) was added and stirred at 65 °C until homogeneous. Then, butyl acrylate (twice the mass of the modified boron nitride nanosheets) and benzoyl peroxide (0.5% of the mass of butyl acrylate) were added and stirred at 70 °C for 4 h. After the reaction was completed, phthalimide diisocyanate (0.2% of the mass of polyisobutylene succinimide) was added and stirring was continued for 2 h. Finally, the obtained product was centrifuged, washed with toluene solvent, and vacuum dried at 60 °C to obtain oleophilic modified boron nitride nanosheets.

[0050] Preparation of a narrow-distribution dual-nano composite detergent: The following components were weighed by weight: 45 parts of high-alkalinity alkyl sulfonate calcium (total alkalinity 340 mgKOH / g), 35 parts of medium-alkalinity alkyl salicylate calcium (total alkalinity 200 mgKOH / g), 5 parts of lipophilic modified nano-boron nitride (average particle size 50 nm), 5 parts of narrow-distribution nano-calcium carbonate (average particle size 30 nm, polydispersity index PDI ≤ 0.3), and 10 parts of alkyl aromatic hydrocarbon co-dispersant (C12 alkylbenzene). Under nitrogen protection, the high-alkalinity alkyl sulfonate calcium and medium-alkalinity alkyl salicylate calcium were added to a reaction vessel according to the specified ratio, and low-temperature dehydration was carried out at 80℃ to obtain the base composite system. The lipophilic modified nano-boron nitride and narrow-distribution nano-calcium carbonate were pre-dispersed ultrasonically in 5 parts of the alkyl aromatic hydrocarbon co-dispersant to form two pre-dispersed suspensions: a lipophilic modified nano-boron nitride suspension and a narrow-distribution nano-calcium carbonate suspension. Under stirring conditions, the two pre-dispersed nano-suspensions were added to the substrate composite system in steps, and then treated with a high-speed homogenization stirring dispersion process at 6000 rpm for 70 min to obtain composite detergent I.

[0051] Comparative Example 2: Compound Detergent II and its Preparation Preparation of lipophilic modified boron nitride nanosheets: Hexagonal boron nitride powder (200 nm in diameter) was dispersed in a 6 mol / L sodium hydroxide solution at a mass-volume ratio of 1 g: 20 mL. The mixture was subjected to a hydrothermal reaction at 100 °C for 15 h in a hydrothermal reactor to hydrolyze some of the BN bonds on the surface to form boron hydroxyl active sites. After the reaction was completed, the product was washed with deionized water until neutral and then vacuum dried at 60 °C to obtain hydroxylated boron nitride nanosheets. The obtained hydroxylated boron nitride nanosheets were dispersed in toluene at a mass-to-volume ratio of 1 g: 40 mL. Polyisobutylene succinimide (18% of the mass of the modified boron nitride nanosheets) was added and stirred at 65 °C until homogeneous. Then, butyl acrylate (twice the mass of the modified boron nitride nanosheets) and benzoyl peroxide (0.5% of the mass of butyl acrylate) were added and stirred at 70 °C for 4 h. After the reaction was completed, phthalimide diisocyanate (0.2% of the mass of polyisobutylene succinimide) was added and stirring was continued for 2 h. Finally, the obtained product was centrifuged, washed with toluene solvent, and vacuum dried at 60 °C to obtain oleophilic modified boron nitride nanosheets.

[0052] Preparation of a narrow-distribution dual-nano composite detergent: The following components were weighed by weight: 45 parts of high-alkalinity alkyl sulfonate calcium (total alkalinity 340 mgKOH / g), 35 parts of medium-alkalinity alkyl salicylate calcium (total alkalinity 200 mgKOH / g), 5 parts of lipophilic modified nano-boron nitride (average particle size 50 nm), 5 parts of narrow-distribution nano-calcium carbonate (average particle size 30 nm, polydispersity index PDI ≤ 0.3), and 10 parts of alkyl aromatic hydrocarbon co-dispersant (C12 alkylbenzene). Under nitrogen protection, the high-alkalinity alkyl sulfonate calcium and medium-alkalinity alkyl salicylate calcium were added to a reaction vessel according to the specified ratio, and low-temperature dehydration was carried out at 80℃ to obtain the base composite system. The lipophilic modified nano-boron nitride and narrow-distribution nano-calcium carbonate were pre-dispersed ultrasonically in 5 parts of the alkyl aromatic hydrocarbon co-dispersant to form two pre-dispersed suspensions: a lipophilic modified nano-boron nitride suspension and a narrow-distribution nano-calcium carbonate suspension. Under stirring conditions, the two pre-dispersed nano-suspensions were added to the substrate composite system in steps, and then treated with a high-speed homogenization stirring dispersion process at 6000 rpm for 70 min to obtain composite detergent II.

[0053] Comparative Example 3: Compound Detergent III and its Preparation Preparation of modified boron nitride nanosheets: Hexagonal boron nitride powder (200 nm in diameter) was dispersed in a 6 mol / L sodium hydroxide solution at a mass-volume ratio of 1 g: 20 mL. The mixture was subjected to a hydrothermal reaction at 100 °C for 15 h in a hydrothermal reactor to hydrolyze some of the BN bonds on the surface to form boron hydroxyl active sites. After the reaction was completed, the product was washed with deionized water until neutral and then vacuum dried at 60 °C to obtain hydroxylated boron nitride nanosheets. The obtained hydroxylated boron nitride nanosheets were dispersed in toluene at a mass-to-volume ratio of 1 g: 30 mL to obtain a boron nitride suspension. 3,3',5,5'-sulfinyl diisophthalic acid (0.4 times the mass of the hydroxylated boron nitride nanosheets) and dimethyldiethoxysilane (0.3% of the mass of the hydroxylated boron nitride nanosheets) were added to the obtained boron nitride suspension and stirred at 70 °C under a nitrogen atmosphere for 8 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. Deionized water was added to the obtained precipitate and the mixture was sonicated at 700 W for 20 min. Finally, the mixture was filtered and dried to obtain modified boron nitride nanosheets.

[0054] Preparation of a narrow-distribution dual-nano composite detergent: The following components were weighed by weight: 45 parts of high-alkalinity alkyl sulfonate calcium (total alkalinity 340 mgKOH / g), 35 parts of medium-alkalinity alkyl salicylate calcium (total alkalinity 200 mgKOH / g), 5 parts of lipophilic modified boron nitride nanosheets, 5 parts of narrow-distribution nano-calcium carbonate (average particle size 30 nm, polydispersity index PDI ≤ 0.3), and 10 parts of alkyl aromatic hydrocarbon dispersant (C12 alkylbenzene). Under nitrogen protection, the high-alkalinity alkyl sulfonate calcium and medium-alkalinity alkyl salicylate calcium were added to a reaction vessel according to the specified ratio, and low-temperature dehydration was carried out at 80℃ to obtain the base composite system. The modified boron nitride nanosheets and narrow-distribution nano-calcium carbonate were pre-dispersed ultrasonically in 5 parts of the alkyl aromatic hydrocarbon dispersant to form two pre-dispersed suspensions: a modified boron nitride nanosheet suspension and a narrow-distribution nano-calcium carbonate suspension. Under stirring conditions, the two pre-dispersed nano-suspensions were added to the substrate composite system in steps, and then treated with a high-speed homogenization stirring dispersion process at 6000 rpm for 70 min to obtain composite detergent III.

[0055] Comparative Example 4: Compound Detergent IV and its Preparation Preparation of a narrow-distribution dual-nano composite detergent: The following components were weighed by weight: 45 parts of high-alkalinity alkyl sulfonate calcium (total alkalinity 340 mgKOH / g), 35 parts of medium-alkalinity alkyl salicylate calcium (total alkalinity 200 mgKOH / g), 5 parts of hexagonal boron nitride powder (particle size 200 nm), 5 parts of narrow-distribution nano-calcium carbonate (average particle size 30 nm, polydispersity index PDI ≤ 0.3), and 10 parts of alkyl aromatic hydrocarbon dispersant (C12 alkylbenzene). Under nitrogen protection, the high-alkalinity alkyl sulfonate calcium and medium-alkalinity alkyl salicylate calcium were added to a reaction vessel according to the specified ratio and subjected to low-temperature dehydration at 80℃ to obtain the base composite system. Hexagonal boron nitride and narrow-distribution nano-calcium carbonate were pre-dispersed ultrasonically in 5 parts of the alkyl aromatic hydrocarbon dispersant to form two pre-dispersed suspensions: a hexagonal boron nitride suspension and a narrow-distribution nano-calcium carbonate suspension. Under stirring conditions, the two pre-dispersed nano-suspensions were added to the substrate composite system in steps, and then treated with a high-speed homogenization stirring dispersion process at 6000 rpm for 70 min to obtain composite detergent IV.

[0056] Comparative Example 5: Composite Detergent V and its Preparation The only difference between this comparative example and Example 1 is that no detergent with narrowly distributed nano-calcium carbonate was added; otherwise, it is the same as Example 1, resulting in composite detergent V.

[0057] Comparative Example 6: Compound Detergent VI and its Preparation The only difference between this comparative example and Example 1 is that no lipophilic modified nano boron nitride was added; otherwise, it is the same as Example 1, resulting in composite detergent VI.

[0058] Comparative Example 7: Compound Detergent VII and its Preparation The only difference between this comparative example and Example 1 is that narrowly distributed nano-calcium carbonate and lipophilic modified nano-boron nitride were not added; otherwise, they are the same as in Example 1, resulting in composite detergent VII.

[0059] Experiment 1: Performance Testing The detergents obtained in Examples 1-3 and Comparative Examples 1-7 were added to the same base oil (API Group III base oil, kinematic viscosity of 4.0-4.5 cSt at 100°C) at a mass ratio of 4.5%, and were combined with conventional lubricating oil additives (antioxidants, anti-wear agents, pour point depressants, etc.) to prepare a lubricating oil composition. The formulation of the lubricating oil composition is shown in Table 1.

[0060] Table 1. Lubricating oil compositions containing compound detergents ; The preparation method of the lubricating oil composition containing a compound detergent includes the following steps: (1) Base oil preheating: Heat the API Group III base oil to 60°C and keep it at a constant temperature under stirring conditions.

[0061] (2) Add hydrogenated styrene-diene copolymer and polymethyl methacrylate sequentially under stirring conditions, and stir for 25 minutes until completely dissolved.

[0062] (3) Add the composite cleaning agent (Examples 1-3 and Comparative Examples 1-7) and bis(succinimide) ashless dispersant, and continue stirring for 35 min.

[0063] (4) Add ZDDP and octylbutyldiphenylamine in sequence and stir at 70°C for 20 min.

[0064] (5) Finally, add dimethyl silicone oil and continue stirring for 15-20 minutes until the system is homogeneous.

[0065] (6) The components were processed at 4000 rpm for 30 min using a high-speed shear homogenizer to ensure that each component was fully dispersed, and a lubricating oil composition containing a composite detergent was obtained.

[0066] The performance was then evaluated according to SH / T 0300 "Crankcase Simulation Test Method (QZX Method)". Simultaneously, the detergent micelle size distribution, high-temperature storage stability, and ash content were tested, and the results are shown in Table 2.

[0067] Table 2. Performance test results of the detergents in Examples 1-3 and Comparative Examples 1-7 ; Note: The data in the table are the average of three parallel measurements.

[0068] Table 2 shows that the PDI values ​​of the micelles in Examples 1-3 are all between 0.15 and 0.17, indicating an extremely narrow micelle size distribution. The coking amount of the aluminum plate is in the range of 7.6-8.5 mg, far below the limit requirement of SH / T 0300 test (usually ≤25 mg), and the paint film rating is Grade 1, showing excellent anti-sludge deposition performance. No stratification phenomenon was observed after 72 h of high-temperature storage, indicating that the dual nanoparticles are stably dispersed in the micelle system and no agglomeration or sedimentation occurred. The ash content is controlled between 0.62% and 0.68%, meeting the requirements of low-ash environmentally friendly oil standards (usually ≤0.80%). The data of the three sets of examples show good reproducibility, verifying the stability and operability of the technical solution of the present invention. Comparative Example 1 (without hydroxylation activation): The boron nitride surface lacks B-OH active sites, and the silane coupling agent cannot be firmly anchored through BO-Si covalent bonds, making it easy for the subsequent modified layer to fall off during subsequent processing and use. Compared to Example 1, PDI increased from 0.15 to 0.22, coking amount increased from 7.6 mg to 12.8 mg, and the film rating decreased from grade 1 to grade 2. This indicates that even without the hydroxylation step, subsequent silane modification and graft polymerization can still improve the dispersibility of boron nitride to some extent, but the strength and durability of the modified layer are insufficient, and the effective ordering of the micelle structure by the nanoparticles cannot be achieved. Comparative Example 2 (without silane coupling agent modification): Without the inner shell layer of silane coupling agent, the tetracarboxylic ligand cannot be effectively anchored to the surface of boron nitride, and PIBS and the oleophilic polymer brush cannot be stably grafted. PDI increased to 0.28, coking amount was 14.2 mg, and the film rating was grade 2. Compared with Comparative Example 1, the performance further deteriorated, indicating that the role of the silane coupling agent as a "molecular bridge" connecting B-OH and the polymer brush is irreplaceable. Comparative Example 3 (without lipophilic monomer graft polymerization): Without the lipophilic polymer brush shell layer, although the nanoparticles could adhere to the boron nitride surface through the dual-ligand anchoring layer, the lack of a steric hindrance layer extending in the oil phase prevented effective prevention of nanoparticle aggregation and adsorption of sludge particles. The PDI increased to 0.36, coking amount was 15.5 mg, and the paint film rating was 2-3. Notably, the PDI of Comparative Example 3 (0.36) was significantly higher than that of Comparative Example 2 (0.28), indicating that the steric hindrance effect of the lipophilic polymer brush contributed more to micelle regularity than the hydroxylation and silane modification steps. Comparative Example 4 (untreated boron nitride, added directly as raw powder): The untreated hexagonal boron nitride raw powder exhibited extremely poor dispersibility in the oil phase, failing to provide skeletal support and interfacial isolation for the nanoparticles. Instead, its aggregation disrupted the stability of the micelle structure. The PDI reached 0.47, coking amount was 21.3 mg, the paint film rating was 3-4, and significant stratification occurred during high-temperature storage. Comparative Example 5 (without narrow-distribution nano-calcium carbonate): The detergent contained only one type of nanoparticle, lipophilic modified nano-boron nitride. The PDI was 0.31, the coking amount was 15.2 mg, and the paint film rating was 2.Although lipophilic modified nano-boron nitride can regulate micelle structure and provide interfacial isolation to some extent, the lack of alkaline sites of nano-calcium carbonate in neutralizing acidic sludge precursors results in insufficient sludge inhibition, and the amount of coking is almost double that of Example 1 (7.6 mg). Simultaneously, the PDI increased from 0.15 to 0.31, indicating that the ability of a single morphology nanoparticle (plate-like) to regulate micelles is limited. Comparative Example 6 (without lipophilic modified nano-boron nitride): The detergent contained only narrowly distributed nano-calcium carbonate nanoparticles. The PDI was 0.29, the amount of coking was 17.1 mg, and the paint film rating was 2-3. Although nano-calcium carbonate can neutralize acidic substances through its surface alkaline sites, its particle morphology cannot provide skeletal support and steric hindrance effects by interpenetrating between micelles like plate-like boron nitride. Therefore, its ability to narrow the micelle particle size distribution is limited (PDI can only be controlled at 0.29), resulting in insufficient high-temperature anti-deposition performance. Comparative Example 7 (without any nanoparticles): This comparative example is a traditional calcium phosphate / calcium salicylate compound detergent system without any nanoparticles. The micelle size distribution is extremely wide (PDI 0.55), the coking amount on the aluminum plate is as high as 24.4 mg, the paint film rating is the worst level 4, obvious stratification occurs during high-temperature storage, and the ash content is as high as 0.98%. These data fully reflect the shortcomings of existing technologies—traditional compound systems are prone to micelle flocculation and aggregation under high-temperature conditions, and sludge is easily deposited.

[0069] Furthermore, ash content testing results showed that the organic polymer brush layer (tetracarboxylic ligand + silane coupling agent + polyisobutylene succinimide + lipophilic polymer brush + crosslinking agent) coated on the surface of the lipophilic modified boron nitride nanoparticles was almost completely decomposed under sulfate ash test conditions, contributing very little to ash content. Calcium salts in high-alkali calcium sulfonate and calcium salicylate were the main sources of ash. When the modified layer of the boron nitride nanoparticles was intact (as in Example 1), the nanoparticles effectively organized the micelle structure, allowing the calcium salts of the high-alkali components to exist in a more stable micelle form, reducing the exposure of free calcium ions, resulting in the lowest ash content. When the modified layer was incomplete (Comparative Examples 1-4), the nanoparticles could not effectively participate in micelle construction, increasing the free high-alkali components and consequently raising the ash content. When the nanoparticles were completely absent (Comparative Example 7), the high-alkali components existed entirely in the traditional micelle form, resulting in the highest ash content (0.98%).

[0070] Test Example 2: Storage Stability Test of Compound Detergent To evaluate the storage stability of the composite detergent of the present invention, 10 g of each detergent obtained in Examples 1-3 and Comparative Examples 1-7 were mixed evenly with 90 g of 150BS base oil (kinematic viscosity of 30-35 cSt at 100℃), and stored at a constant temperature of 60℃. The changes in the state of the samples at different storage times were recorded. The results are shown in Table 3.

[0071] Table 3. Storage stability test results of detergents in Examples 1-3 and Comparative Examples 1-7 ; As shown in Table 3, the detergents of Examples 1-3 remained uniformly transparent after 60 days of storage at 60°C, without any stratification, sedimentation, or flocculation. The PDI values ​​after 60 days were 0.16, 0.18, and 0.17, respectively, showing almost no change compared to the initial PDI (0.15-0.17). This indicates that the present invention, through the synergistic effect of the core-shell structure design of lipophilic modified boron nitride nanoparticles and nano-calcium carbonate, enables the nanoparticles to achieve long-term stable dispersion in the micelle system. The lipophilic polymer brushes on the surface of the nanoparticles fully extend in the oil phase, forming a strong steric hindrance layer, effectively preventing the aggregation and sedimentation of the nanoparticles. Comparative Example 1 (unhydroxylated): The performance was acceptable within 7 days of storage, but slight turbidity appeared after 15 days, trace sedimentation was visible at the bottom after 30 days, and significant sedimentation occurred after 60 days. Because boron nitride is not activated by hydroxylation, its surface lacks B-OH active sites. The silane coupling agent cannot form BO-Si covalent bonds, relying only on physical adsorption or weak hydrogen bonding. During long-term thermal storage, the modified layer gradually desorbs from the boron nitride surface, leading to the gradual aggregation and sedimentation of nanoparticles. Comparative Example 2 (without silane modification): Slight turbidity appeared after 7 days of storage, trace sedimentation appeared at the bottom after 15 days, significant sedimentation occurred after 30 days, and substantial sedimentation occurred after 60 days. Without a silane coupling agent as a chemical bridging layer, there is a lack of effective chemical connection between the tetracarboxylic ligand and PIBS and the lipophilic polymer brush. The grafting density of the polymer brush on the boron nitride surface is low and the anchoring is weak. Under thermal storage conditions, the polymer brush gradually detaches, and the nanoparticles lose steric protection and aggregate. Comparative Example 3 (without lipophilic monomer graft polymerization): Slight turbidity appeared after 72 hours of storage, trace sedimentation occurred at the bottom after 7 days, and substantial sedimentation occurred after 30 days. Although a dual-ligand anchoring layer has formed on the surface of the nanoparticles, the lack of a hydrophilic polymer brush shell layer means that the nanoparticles lack effective steric hindrance in the oil phase. The limited hydrophilicity of the ligand layer alone cannot maintain long-term stable dispersion, and the nanoparticles rapidly aggregate during thermal storage. Comparative Example 4 (untreated boron nitride): Slight turbidity appeared after 24 hours of storage, trace sedimentation appeared at the bottom after 72 hours, significant sedimentation occurred after 7 days, severe sedimentation occurred after 30 days, and complete stratification occurred after 60 days. The surface of untreated hexagonal boron nitride powder is hydrophilic and cannot be effectively dispersed in non-polar base oils. High-speed homogenization stirring alone cannot maintain long-term stability. Comparative Example 5 (no narrow-distribution nano-calcium carbonate): Good performance was observed within 7 days of storage, but slight turbidity appeared after 15 days, trace sedimentation occurred at the bottom after 30 days, and significant sedimentation occurred after 60 days. Containing only lipophilic modified boron nitride nanoparticles, lacking the synergistic stabilizing effect of nano-calcium carbonate, the total number of nanoparticles in the system is reduced, resulting in insufficient regularity and compactness of the micelle structure. During long-term storage, slow micelle reorganization leads to particle sedimentation. Comparative Example 6 (without lipophilic modified boron nitride nanoparticles): slight turbidity appeared after 7 days of storage, trace sedimentation appeared at the bottom after 15 days, significant sedimentation occurred after 30 days, and substantial sedimentation occurred after 60 days.Containing only narrow-distribution nano-calcium carbonate, this nano-calcium carbonate, despite its narrow particle size distribution, lacks lipophilic surface modification, resulting in insufficient long-term dispersion stability in base oils. Under thermal storage conditions, it gradually aggregates and settles. Comparative Example 7 (without any nanoparticles): After 24 hours of storage, it was uniformly transparent, but slight turbidity appeared after 72 hours, significant sedimentation occurred after 7 days, substantial sedimentation occurred after 15 days, severe sedimentation occurred after 30 days, and complete stratification occurred after 60 days. This comparative example is a traditional calcium phosphate / calcium salicylate compound detergent system, containing no nanoparticles. It has a wide micelle size distribution (initial PDI 0.55) and strong van der Waals forces between micelles. Under thermal storage conditions, the micelles slowly flocculate and aggregate, ultimately leading to macroscopic stratification.

[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the methods and techniques disclosed above without departing from the scope of the present invention to create equivalent embodiments. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A narrow-distribution dual-nano composite detergent, characterized in that, It contains the following raw material components: high-alkali alkyl sulfonate calcium, medium-alkali alkyl salicylate, lipophilic modified nano boron nitride, narrow-distribution nano calcium carbonate and alkyl aromatic hydrocarbon dispersant; The total alkalinity of the high-alkalinity alkyl sulfonate calcium is 280~410 mgKOH / g; The total alkalinity of the medium-alkalinity alkyl salicylate calcium is 150~250 mgKOH / g; The average particle size of the lipophilic modified boron nitride nanoparticles is 20~100 nm; the surface of the lipophilic modified boron nitride nanoparticles has a chemically anchored inner shell layer and a lipophilic polymer brush outer shell layer arranged sequentially from the inside to the outside. The narrow-distribution nano-calcium carbonate has an average particle size of 10~50 nm and a particle size polydispersity index (PDI) ≤0.

3.

2. The narrow-distribution dual-nano composite detergent according to claim 1, characterized in that, The proportions of each component by weight are as follows: 30-60 parts of high-alkalinity alkyl sulfonate calcium, 20-50 parts of medium-alkalinity alkyl salicylate calcium, 1-10 parts of lipophilic modified nano boron nitride, 1-10 parts of narrow-distribution nano calcium carbonate, and 5-10 parts of alkyl aromatic hydrocarbon dispersant.

3. The narrow-distribution dual-nano composite detergent according to claim 1 or 2, characterized in that, The alkyl aromatic hydrocarbon dispersant is selected from one or more of C10-C20 alkylbenzenes and light mineral oils.

4. The narrow-distribution dual-nano composite detergent according to claim 1 or 2, characterized in that, The lipophilic modified boron nitride nanoparticles are prepared according to the following steps: S1: Disperse hexagonal boron nitride powder in a strong alkaline solution at a mass-volume ratio of 1g:10~30mL, and carry out a hydrothermal reaction at 80~120℃ for 6~24 h to hydrolyze some of the BN bonds on its surface to form boron hydroxyl active sites, thereby obtaining hydroxylated boron nitride nanosheets. S2: The obtained hydroxylated boron nitride nanosheets were dispersed in an organic solvent at a mass-volume ratio of 1g:10~50mL to obtain a boron nitride suspension; a tetracarboxylic acid ligand and a silane coupling agent were added to the obtained boron nitride suspension and stirred to react. After the reaction was completed, the mixture was cooled to room temperature and filtered. Water was added to the obtained precipitate and the mixture was sonicated at 600~800W for 10~30min. Finally, the mixture was filtered and dried to obtain modified boron nitride nanosheets. S3: The obtained modified boron nitride nanosheets were dispersed in an organic solvent at a mass-volume ratio of 1g:20~60mL. Polyisobutylene succinimide was added and stirred evenly at 60~65℃. Then, lipophilic monomers and initiators were added and stirred for reaction. After the reaction was completed, crosslinking agent was added and stirring was continued for 1~3h. Finally, the obtained product was centrifuged, washed with solvent and vacuum dried to obtain lipophilic modified boron nitride nanosheets.

5. The narrow-distribution dual-nano composite detergent according to claim 4, characterized in that, In step S1, the strong alkaline solution is selected from sodium hydroxide solution or potassium hydroxide solution, and the concentration is 2~10 mol / L.

6. The narrow-distribution dual-nano composite detergent according to claim 4, characterized in that, In step S2, the organic solvent is selected from toluene, ethanol, and tetrahydrofuran; The tetracarboxylic ligand is selected from any one of 3,3',5,5'-sulfinyl diisophthalic acid, 3,3',5,5'-sulfonyl diisophthalic acid, 3,3',5,5'-azadiisophthalic acid, 3,3',5,5'-oxodiisophthalic acid, 3,3',5,5'-carbonyl diisophthalic acid, and 3,3',5,5'-methylene diisophthalic acid. The amount of the tetracarboxylic ligand added is 0.3 to 0.5 times the mass of the hydroxylated boron nitride nanosheets. The silane coupling agent is selected from one or more of methyltrimethoxysilane, tetramethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltriethoxysilane, and tetrapropoxysilane, and the amount of the silane coupling agent added is 0.1 to 0.5% of the mass of the hydroxylated boron nitride nanosheets.

7. The narrow-distribution dual-nano composite detergent according to claim 4, characterized in that, In step S3, the organic solvent is selected from toluene, ethanol, and tetrahydrofuran; The amount of polyisobutylene succinimide added is 5-30% of the mass of the modified boron nitride nanosheets; The lipophilic monomer is selected from one or more of butyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate, and the amount of the lipophilic monomer added is 1 to 3 times the mass of the modified boron nitride nanosheets. The initiator is selected from one or more of ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, and azobisisobutyronitrile, and the amount of the initiator added is 0.2-0.7% of the mass of the lipophilic monomer; The crosslinking agent is selected from one or more of toluene diisocyanate, chlorophenyl diisocyanate, tetramethylene diisocyanate, phenyl diisocyanate, and diphenylmethane diisocyanate, and the amount of the crosslinking agent added is 0.1 to 0.3% of the mass of polyisobutylene succinimide.

8. A method for preparing a narrow-distribution dual-nano composite detergent as described in any one of claims 1-7, characterized in that, Includes the following steps: (1) Under nitrogen protection, high-base-value alkyl sulfonate calcium and medium-base-value alkyl salicylate calcium are added to the reaction vessel in proportion and dehydrated at low temperature at 60~100℃ to obtain the base compound system; (2) The lipophilic modified boron nitride nanoparticles and narrowly distributed calcium carbonate nanoparticles are pre-dispersed ultrasonically in a portion of alkyl aromatic hydrocarbon dispersant to form two pre-dispersed suspensions, namely lipophilic modified boron nitride nanoparticles and narrowly distributed calcium carbonate nanoparticles suspensions. (3) Under stirring conditions, the two pre-dispersed nano suspensions were added to the substrate compound system in steps, and then the high-speed homogeneous stirring dispersion process was used to treat the mixture at a speed of 3000~10000 rpm for 30~120 min to obtain a narrow distribution dual nano composite detergent.

9. The application of a narrow-distribution dual-nano composite detergent as described in any one of claims 1-7 in lubricating oil, characterized in that, The detergent is added to the base oil at a mass ratio of 3.0% to 6.0% and used in conjunction with conventional lubricating oil additives.

10. The application according to claim 9, characterized in that, The lubricating oil is an internal combustion engine oil, and the detergent is used to improve the sludge deposition performance of the crankcase. In the SH / T 0300 crankcase simulation test, the coking amount of aluminum plate of the lubricating oil with the detergent added is ≤10 mg and the paint film rating is ≤2 grade.